THE MODEL OF CRIMINAL ACTIVITY AND EFFECTIVE CARTEL DETERRENCE - Klimašauskienė, Danguolė (Ekonomika, 2014)
Cartels, or secret agreements between competitors, are universally recognized as the most harmful of all types of anticompetitive conduct. Facing the challenges associated with globalization of the market economy, competition authorities in all parts of the world are increasing their efforts to design and implement modern instruments, effective enforcement procedures and adequate sanctions in order not only to detect and punish, but also to deter cartels.In this paper, we analyze the deterrent properties of the competition policy within the legal framework of the European Union. Applying the classical deterrence theory based on the model of criminal activity, we identify two key factors that affect the degree of deterrence of anticompetitive behavior: adequate sanctions and the probability of detection. We further discuss the level of fines, leniency programs and direct settlement procedures, both the latter as instruments to enhance the probability of cartel detection.By employing the methods of meta-analysis and meta-synthesis of economic and legal literature, cartel case studies, and descriptive statistical analysis, our attempt is to show that during the past decades the European competition authorities have focused on efforts to increase the effectiveness of cartel prosecution and to achieve better deterrence by numerous alterations in the European competition law, such as extensions of the fine spectrum or leniency programs or introduction of a direct settlement procedure, and that these efforts have proven to be rather successful for preventing the formation of anticompetitive agreements.